Emotional distress drives health services overuse in patients with acute low back pain: a longitudinal observational study - Traeger, Adrian C.; Hübscher, Markus; Henschke, Nicholas; Williams, Christopher M.; Maher, Christopher G.; Moseley, G. Lorimer; Lee, Hopin; McAuley, James H. (European spine journal, 2016)
To determine whether emotional distress reported at the initial consultation affects subsequent healthcare use either directly or indirectly via moderating the influence of symptoms.
Gesehen am 27.05.2020